SnO2‐in‐Polymer Matrix for High‐Efficiency Perovskite Solar Cells with Improved Reproducibility and Stability. Issue 52 (2nd November 2018) - Wei, Jing; Guo, Fengwan; Wang, Xi; Xu, Kun; Lei, Ming; Liang, Yongqi; Zhao, Yicheng; Xu, Dongsheng
Abstract: Understanding interfacial loss and the ways to improving interfacial property is critical to fabricate highly efficient and reproducible perovskite solar cells (PSCs). In SnO2 ‐based PSCs, nonradiative recombination sites at the SnO2 –perovskite interface lead to a large potential loss and performance variation in the resulting photovoltaic devices. Here, a novel SnO2 ‐in‐polymer matrix (i.e., polyethylene glycol) is devised as the electron transporting layer to improve the film quality of the SnO2 electron transporting layer. The SnO2 ‐in‐polymer matrix is fabricated through spin‐coating a polymer‐incorporated SnO2 colloidal ink. The polymer is uniformly dispersed in SnO2 colloidal ink and promotes the nanoparticle disaggregation in the ink. Owing to polymer incorporation, the compactness and wetting property of SnO2 layer is significantly ameliorated. Finally, photovoltaic devices based on Cs0.05 FA0.81 MA0.14 PbI2.55 Br0.45 perovskite sandwiched between SnO2 and Spiro‐OMeTAD layer are fabricated. Compared with the averaging power conversion efficiency of 16.2% with 1.2% deviation for control devices, the optimized devices exhibit an improved averaging efficiency of 19.5% with 0.25% deviation. The conception of polymer incorporation in the electron transporting layer paves a way to further increase the performance of planar perovskite solar cells. Abstract : A novel SnO2 ‐in‐polymer matrix is demonstrated to be an excellent electron‐selective layer in perovskite solar cells. The polymer is uniformly dispersed in SnO2 colloidal ink and promotes the nanoparticle disaggregation in the ink. Planar‐structure perovskite solar cells based on this SnO2 ‐in‐polymer matrix show a high efficiency of 20.8% with negligible hysteresis and superior reproducibility.